Penyuluhan standar kecukupan gizi pada konsumsi rumah tangga dan jajanan sekolah - Yahmi Ira Setyaningrum; Kanthi Arum Widayati; Tinia Leyli Shofia Ahmad; Sri Suripti (Poltekkes Kemenkes Yogyakarta, 2021)
The COVID-19 pandemic has spread widely in Indonesia, so efforts are needed to improve the immune system through adequate nutrition. The purpose of the STIKes Widya Cipta Husada Nutrition Study Program community service activity in collaboration with the DKI Jakarta MGMP Biology MA and the Biology Department of IPB is to increase teacher knowledge about nutritional adequacy standards. Method used is an online lecture, knowledge score measure by questioner google form. The training was proven to be able to increase participants' knowledge by 8.42 points. The average value of participants' knowledge before the training was 63.01, while the score after the training increased to 71.43. The evaluation of the seminar participants stated that the event was going well with an average score of 3.5 (highest scale 4). The speaker gave the material well with an average score of 3.7 (scale 4). The material provided is easy to understand with a score of 3.6 (scale 4). The committee was very helpful in the smooth process of the webminar with an average score of 3.5 (scale 4). Participants were satisfied after participating in the webminar with an average score of 3.5 (scale 4). The pre-test and post-test questions represent the material with an average score of 3.6 (scale 4). New webminar participants know the nutritional adequacy rate standard, and it will be delivered to their students. The importance of this community service program as a health promotion to convey a message of balanced nutrition.